Autonomously hyperfunctioning cystic nodule harbouring thyroid carcinoma – Case report and literature review. (2018) - Lima, Maria João; Soares, Virgínia; Koch, Pedro; Silva, Artur; Taveira-Gomes, António
Highlights: Hyperthyroidism cannot rule out thyroid cancer. Published cases of autonomously functioning thyroid carcinomas are increasing. In hyperthyroid patients, carcinoma should always be considered as differential diagnosis. Abstract: Introduction: Hyperthyroidism is rarely associated with malignancy, but it cannot rule out thyroid cancer. Although there is published data describing this coexistence, thyroid carcinomas inside autonomously functioning nodules are uncommon. Presentation of case: A 49-year-old woman presented with a cervical mass, unexplained weight loss and anxiousness, sweating and insomnia. On physical examination, she had a palpable left thyroid nodule. Thyroid function tests showed suppressed TSH (<0, 1 uUI/mL), thyroxine 1, 44 ng/dL (normal range 0, 70–1, 48) and triiodothyronine 4, 33 pg/mL (normal range 1, 71–3, 71). Ultrasound imaging revealed a left lobe, 4 cm partial cystic nodule. 99mTC thyroid scintigraphy showed a hyperfunctioning nodule with suppression of the remainder parenchyma. Fine-needle aspiration cytology was nondiagnostic (cystic fluid). The patient was started on thiamazole 5 mg daily with subsequent normalization of thyroid function, but she developed cervical foreign body sensation and a left hemithyroidectomy was performed. Histology showed a 4 cm cystic nodule with a follicular variant papillary carcinoma and the patient underwent completion thyroidectomy, followed by radio-iodine ablation. Discussion: Published literature showed an increased prevalence of autonomously functioning nodules, harbouring thyroid carcinomas in adults. Papillary carcinoma is the most frequently described but the follicular variant is rare. Conclusion: Although rare, thyroid cancer is not definitively excluded in hyperthyroid patients and it should always be considered as differential diagnosis.